2008
DOI: 10.1038/gt.2008.150
|View full text |Cite
|
Sign up to set email alerts
|

Correction of dystrophia myotonica type 1 pre-mRNA transcripts by artificial trans-splicing

Abstract: Dystrophia myotonica type 1 (DM1), the most common muscular dystrophy in adults, results from expansion of a CTG repeat in the 3 0 -untranslated region of the dystrophia myotonica protein kinase gene (DMPK). Correction of the mutant DMPK transcript is a potential therapeutic strategy in DM1. We investigated the efficacy of artificial trans-splicing molecules (ATMs) to target and correct DMPK transcripts. ATMs designed to target intron 14 of DMPK pre-mRNA transcripts were tested for their ability to trans-splic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 26 publications
(40 reference statements)
0
16
0
Order By: Relevance
“…Trans-splicing has restored factor VIII expression in a hemophilia A knock out mouse model, generating F8 levels above 20% of normal 13 . We and others have shown that RNA trans-splicing can rewrite genes that cause a wide range of diseases including spinal motor atrophy 14 , myotonic dystrophy 15 , epidermolysis bullosa 16,22 , cancer 17,18 and sickle cell anemia 23 . More recently, mRNA and protein expression were corrected in the brains of a mouse model of tau mis-splicing by RNA trans-splicing 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Trans-splicing has restored factor VIII expression in a hemophilia A knock out mouse model, generating F8 levels above 20% of normal 13 . We and others have shown that RNA trans-splicing can rewrite genes that cause a wide range of diseases including spinal motor atrophy 14 , myotonic dystrophy 15 , epidermolysis bullosa 16,22 , cancer 17,18 and sickle cell anemia 23 . More recently, mRNA and protein expression were corrected in the brains of a mouse model of tau mis-splicing by RNA trans-splicing 24 .…”
Section: Discussionmentioning
confidence: 99%
“…This is much higher than what has been reported in previous studies using endogenous targets. 5,33 However, despite the high efficiency of Mybpc3 5â€Č- trans -splicing at the mRNA level, the amount of repaired cMyBP-C protein was rather low. This suggests a low efficiency of translation and underlines that mRNA copy number and protein levels do not need to be correlated.…”
Section: Discussionmentioning
confidence: 99%
“…The defective portion of the target premRNA is removed and replaced with a wild-type cDNA exon contained within the PTM, and a functional gene product is transcribed. The use of SmaRT for the functional correction of a number of disease mutation models has been reported (Mansfield et al, 2000;Liu et al, 2002b;Chao et al, 2003;Tahara et al, 2004;Chen et al, 2009). Using a double transsplicing approach, it has been shown that replacement of the mutated mdx exon 23 was achievable in the mRNA target (Lorain et al, 2010).…”
Section: Spliceosome-mediated Rna Trans-splicingmentioning
confidence: 98%